Recommended dietary allowances (National Academy Press, 1989)
Defnition and Applications -- Energy -- Carbohydrates and Fiber -- Lipids -- Protein and Amino Acids -- Fat-Soluble Vitamins -- Water-Soluble Vitamins -- Minerals -- Trace Elements -- Water and Electrolytes -- Other Substances in Food.